Responsabilidade social da CI na inclusão de comunidades na sociedade da informação - Farias, Maria Giovanna Guedes (2011)
This study is founded on the social responsibility of the Information Science (IS) for inclusion of communities in the information society. Discusses the role of IS in delineating ways for the social inclusion through digital inclusion by access to digital technologies of communication and information. The intervention happened, in the Comunidade Santa Clara (CSC), in João Pessoa-PB, through field research for registration, organization and dissemination of „information sources‟ (study subjects) comprised of people of the Community. An action of information has been implemented into the CSC to create the virtual interface „Blog da Comunidade Santa Clara‟ in the Wordpress platform, to disseminate the wealth of knowledge of those depositors of social memory and knowledge of Santa Clara, which will be available for future generations.